Research on production of protein feed from waste food fermented by multi-strains - CHEN Gui-cai; DAI De-hui; HUANG Guang-rong; HU Wei-lian (浙江大学学报. 农业与生命科学版)
By a serial of single factors and orthogonal design (L9 34) tests, the fermentation conditions of producing protein feed from waste food were optimized. Results showed that the optimal conditions were: fermentation time 24 h, Candida utilis C01: Saccharomyces cerivisiae S0201: Lactobacillus plantarum L0211 6∶3∶1, (NH4)2 SO4 2.5%, waste food∶wheat bran 6∶4, inoculum size 3%, fermentation temperature 30℃. Under optimized conditions, the true protein content and the increase rate of true protein after fermentation were 18.02% and 75.84%, respectively. Enlarged scale tests revealed that true protein content and the increase rate of true protein under controlled fermentation temperature were 17.56% and 71.35%, respectively, much higher than those without controlled (12.45%, 21.25%). Chemical analyzing of final product showed that its chief constituents were saccharide, crude protein and crude fattiness, their contents were 32.24%, 26.21% and 20.23%, respectively.